Prednisone Pharmacokinetics During Pregnancy and Lactation. (7th May 2018) - Ryu, Rachel J.; Easterling, Thomas R.; Caritis, Steve N.; Venkataramanan, Raman; Umans, Jason G.; Ahmed, Mahmoud S.; Clark, Shannon; Kantrowitz‐Gordon, Ira; Hays, Karen; Bennett, Brooke; Honaker, Matthew T.; Thummel, Kenneth E.; et al.
Abstract: To evaluate the steady‐state pharmacokinetics of prednisone and its metabolite prednisolone in pregnant and lactating female subjects, 19 subjects received prednisone (4‐40 mg/day orally) in early (n = 3), mid (n = 9), and late (n = 13) pregnancy as well as postpartum with (n = 2) and without (n = 5) lactation. Serial blood and urine samples were collected over 1 dosing interval. Prednisone and its metabolite, prednisolone, steady‐state noncompartmental pharmacokinetic parameters were estimated. During pregnancy, prednisone apparent oral clearance increased with dose (35.1 ± 11.4 L/h with 5 mg, 52.6 ± 5.2 L/h with 10 mg, and 64.3 ± 6.9 L/h with 20 mg, P  = .001). Similarly, unbound prednisone apparent oral clearance increased with dose. In addition, prednisolone renal clearance increased with dose (0.3 ± 0.3 L/h with 5 mg, 0.5 ± 0.4 L/h with 10 mg, and 1.3 ± 1.1 L/h with 20 mg, P  = .002). Higher prednisone (r = 0.57, P ≤ .05) and prednisolone (r = 0.75, P ≤ .05) concentrations led to a higher percentage of unbound drug. Breast‐milk/plasma area under the concentration‐time curve ratios were 0.5‐0.6 for prednisone and 0.02‐0.03 for prednisolone. Relative infant doses were 0.35% to 0.53% and 0.09% to 0.18%, for prednisone and prednisolone, respectively. Prednisone and prednisolone exhibit dose‐ and concentration‐dependent pharmacokinetics during pregnancy, and infant exposure to these agents via breast milk is minimal.